Emotion: The Connective Tissue of Atmospheres and Haunts - Jawer, Michael (Journal of Scientific Exploration, 2023)
Just as a small band of scholars has endeavored to explore the phenomenon of “atmosphere” – i.e., the characteristic feel of a particular situation, circumstance, artifact or era – another group of researchers has shed light on the defining characteristics of “haunts,” those places where the atmosphere may, to some people, seem strange, spooky or off-putting. The fields of atmosphere studies, hauntology, and spectrality attest to these investigations. However, scholars of atmosphere rarely refer to haunts, while scholars of hauntology and spectrality insufficiently emphasize the affective core of atmospheres. This paper argues that affect – which nearly all studies acknowledge as the key element of atmosphere – is equally central to the phenomenon of haunts. Since affect is a property of living creatures, the paper proposes that haunted atmospheres attest to the quality or intensity of feelings expressed by individuals, even if they are no longer in that location or no longer living. Just as atmospheres can be sensed but not grasped, just as they are ineffable yet discernable, and just as they are fleeting yet can also linger, they resemble feelings, moods and ghosts. The term “presence,” which recurs throughout atmosphere studies, hauntology, and spectrality, is closely considered for its connection with concepts of time, immediacy, and memory. Three experiences of the author are presented as touchstones for evaluating the possibilities discussed. The paper concludes by discussing our species’ “ocular-centrism,” i.e., its tendency to conclude that what can be seen and definitively measured is real whereas what is invisible and shifting is less real or not at all.